Atypical extragingival occurrence of lobular capillary hemangioma: A report of two cases - Sneha R Sharma; Archana Mehra; Freny R Karjodkar; Kaustubh P Sansare (Wolters Kluwer Medknow Publications, 2021)
Capillary hemangiomas and pyogenic granuloma (PG) are well-recognized benign entities of the oral cavity which are vascular in origin. PG is said to have a predilection for gingival area, whereas capillary hemangioma involves the lips, cheek, and tongue. They may mimic more serious conditions such as malignancies making the clinical diagnosis quite challenging. There have been cases reported where PG was found on extra-gingival sites such as the palate, lips, and tongue. We present the two cases of lobular capillary hemangioma (LCH) on extragingival sites, namely the palate and buccal mucosa, which manifested as a different lesion clinically and histopathological examination was indicative of LCH. The cases reported here show that relatively common pathologies can present on rare or atypical regions inside the oral cavity, and hence, it is imperative for the clinician to consider such lesions while formulating a diagnosis.